قصيدة بانت سعاد (قصيدة البردة) لكعب بن زهير: دراسة تحليلية عروضية: Banat Su’ad – Burdah Poem – Ka’ab Bin Zuhayr – Poetic meter – Themes - Mohd Sanadi, Aida Hayati; Ahmad Safian, Nursafira (Al-Ḍād Journal, 2019)
The main objective of this research is to reveal the themes and musical melodies in Burdah poem or Banat Su’ad poem, written by Ka’ab Bin Zuhayr. The researchers make use in the study descriptive and analytical methods, in which they present briefly an overview of the poet’s background at the beginning of the study. Then, they analyze the themes of the poem as well as its musical melodies using prosodic analysis in order to determine the meter of the poem, highlighting the correlation between the both. The rhyme of Burdah poem is lāmiyah maḍmūmah and it is using basīṭ meter. The arūḍ of this poem is makhbūnah, in other words the letter of alif being deleted; hence, it changes from fā‘ilun (فَاعِلُن) to fa‘ilun (فعِلن). The researchers found that the poet used al-bayt al-muṣarra’, in which the ‘arūḍ was changed to match the meter and rhyme of the ḍarab. This usually happens at the beginning of the poem to draw the attention of the reader that the poet had just started his poem. Apart from that, this study found that the poet used basīṭ meter as it matches the theme of apology and compliment. He chose the rhyme of al-lām al-muṭlaqah for his poem, since it gave strong personal impression. Besides, there are internal melodies embedded in the poem; because of the best-selected words were used, the vigorous relation between the meaning and the beauty of depiction.